The Analysis Study of Incidence, Indications, Risk Factor, Management and Outcomes of Emergency Hysterectomy: A Comprehensive Systematic Review - Niken Septia Nita; Putra Ismaya Abral (International Medical Journal Corp. Ltd, 2024)
Background: Extirpation of the uterus during the puerperium, after vaginal delivery, or after a caesarean section is known as an emergency obstetric hysterectomy (EOH). It is typically carried out when obstetric haemorrhage is severe and life-threatening. A woman who almost died but survived a pregnancy-related or childbirth-related issue, or within 42 days of the pregnancy ending, is said to have experienced a near-miss episode. The aim: The aim of this study to show about incident, indications, risk factor, management and outcomes of emergency hysterectomy. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: In obstetrics, emergency obstetric hysterectomy (EOH) is a necessary evil. In many instances, it saves the mother's life, even though it limits the woman's future ability to bear children. Rather than the treatment itself, the majority of its morbidity is caused by its indications and underlying illnesses.